Burden of mortality related to pregnancy, childbirth and the puerperium. Cuba 2005-2018 - Delia María Galvez Medina; Lisbeth Fernández González; Armando Humberto Seuc Jo; José Luis Peñalvo García; Miguel Ángel Martínez Morales; Vivian Herrera Gómez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: maternal death represents one of the most notable events in the conflicts of sexual and reproductive health in the world. The high mortality from this cause in the world is unacceptable. However, estimates for determining the burden of maternal morbidity and mortality health are still limited. Objective: to determine the burden of mortality related to pregnancy, childbirth and the puerperium in Cuba between 2005 and 2018. Methods: a descriptive study was carried out, with national cross-sectional data and annual periodicity. The universe of study was made up of all the deaths that occurred during pregnancy, childbirth and the puerperium in the period 2005-2018, in Cuba (N = 831). The mortality ratio, years of life potentially lost due to mortality, the percentage, the average and the trend were calculated. Results: of the total number of deceased due to deaths that occurred during pregnancy, childbirth and the puerperium, 463 were due to direct death; 247 for indirect death; and 247, due to other deaths 121. The ratio averaged 48.8 deaths for every 100 000 live births. Years of life potentially lost were 42,582: 23,433 for direct deaths, 12,724 for indirect deaths, and 6,425 for other deaths. Conclusion: direct obstetric deaths were the most frequent and those with the greatest impact on life expectancy; while indirect obstetrician women showed a tendency to increase over time. For other deaths, women died at an earlier age.